Reflective practice in English language teacher training: From theory to practice - Phan Thi Thu Nga (Ho Chi Minh City Open University Journal of Science - Social Sciences, 2019)
The main aim of the study presented in this article is examining what teacher-trainees could learn from the reflective practice task after their teaching performance in the English Teaching Practice Course. Participants of this study were teacher-trainees (or senior students majoring in English language teaching) in the first semester of academic year 2018-2019. Each trainee had his/her lesson recorded when s/he was conducting an English lesson in front of his/her peers. Then each watched the lesson and found some strengths and weaknesses in this lesson and submitted this task to the trainer. The findings from this reflective task indicated that trainees could recognize not only their errors in using classroom English but also four main weaknesses in their teaching skills. Moreover, the findings from the questionnaire after the course ended reveal that these trainees classified their errors into seven groups and suggested solutions to overcome such problems. Some limitations and recommendations for further study on reflection can be seen at the end of this article.